Legal Protection of Secured Creditors in Contemporary Bankruptcy: A Comparative Study of Positive Law and Islamic Law - Yuhelson; Nur Hakim (Faculty of Sharia, IAIN Metro, 2025)
This article examines the legal protection of secured creditors in contemporary bankruptcy, particularly concerning the execution of collateral during insolvency and the scope of their preferential rights. Under Article 55(1) of Law No. 37 of 2004 on Bankruptcy, secured creditors are granted an exception to the principle of general attachment (sita generalis). The central issue addressed is the extent to which these execution rights may be restricted in practice and how judicial decisions establish legal precedents regarding the sale of collateral. The study employs a normative legal research method combined with a comparative approach, analysing Indonesian positive law alongside Islamic law. Data were obtained through an extensive review of statutory regulations, court decisions, and classical and contemporary Islamic jurisprudence. The findings indicate that although secured creditors hold preferential rights, these rights are not absolute. Unilateral auction sales conducted without curator involvement may be deemed unlawful, as they conflict with the principle of general attachment and undermine the curator’s authority in managing the bankruptcy estate, thereby disadvantaging other creditors. Accordingly, the research underscores the importance of coordination between secured creditors and curators to safeguard the collective interests of all creditors. The article’s academic contribution lies in its comparative analysis, which integrates Indonesian positive law with Islamic law's ethical and justice-oriented principles. By addressing legal certainty and humanitarian values, the study provides fresh insights into protecting secured creditors in bankruptcy. Ultimately, it contributes to the broader discourse on developing fairer, more inclusive, and socially responsive bankruptcy regulations within Indonesia’s plural legal framework.